Production of phytoestrogens by plant cell and tissue cultures: recent scenario and exciting prospects. - Shinde, Amit N.; Malpathak, Nutan; Fulzele, Devanand P. (Pharmacognosy Reviews)
Phytoestrogens are group of plant derived compounds structurally and functionally mimic mammalian estrogen. Phytoestrogenic isoflavones, daidzein and genistein are associated with several health promoting properties against sex hormone related ailments and cancer. They are restricted to leguminoceae family and often subjected genotype and environment dependant variation in accumulation. Plant cell cultures have higher rate of metabolism and condensed biosynthetic rate, resulted in shorter period of time required for secondary metabolite production compared to intact plants. In present review we have summarized various studies carried out for production of isoflavones by in vitro cell cultures. Additionally several product optimization strategies including manipulation of physical and chemical parameters, elicitation, permeabilization and bioreactor application for mass cultivation were discussed with respect to isoflavonoids production. Advances in functional and structural genomics has resulted in identification and cloning of relevant genes from isoflavone biosynthetic pathway and regulatory systems. Metabolic engineering has improved productivity of plant cell cultures, intact plants and resulted in fortification of isoflavones in several legumes and non leguminous plants. This review highlights recent trends and future prospects of various strategies to direct higher than average productivity of phytoestrogenic isoflavones in plant cell cultures.
Keywords: Plant cell cultures; phytoestrogens; elicitation; bioreactor; metabolic engineering